Gendering the Internet: Perempuan pada Ruang Gender yang Berbeda - Rina Sari Kusuma; Yuan Vitasari (FISIP Universitas Atma Jaya Yogyakarta, 2017)
Media becomes the mirror of society and refl ects what happened within. Study of gender cannot be separated from technology, which by gender is both shaping and shaped by internet. In Indonesia, there are many websites that segmented based on gender (gender space), such as Vemale.com and Sooperboy.com. This research aims to seek the representation of women in these different gendered spaces. Using qualitative approach with qualitative content analysis as the methodology, the result shows that the websites already represent women in public space, even though it is still overshadowed by the domestic rules of women in private space.